2020
DOI: 10.3390/en13184815
|View full text |Cite
|
Sign up to set email alerts
|

Application of Photovoltaic Systems for Agriculture: A Study on the Relationship between Power Generation and Farming for the Improvement of Photovoltaic Applications in Agriculture

Abstract: Agrivoltaic (agriculture–photovoltaic) or solar sharing has gained growing recognition as a promising means of integrating agriculture and solar-energy harvesting. Although this field offers great potential, data on the impact on crop growth and development are insufficient. As such, this study examines the impact of agriculture–photovoltaic farming on crops using energy information and communications technology (ICT). The researched crops were grapes, cultivated land was divided into six sections, photovoltai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
0
25
0
5
Order By: Relevance
“…Bulgari et al [146] also found a lower content of quality parameters for tomatoes with a configuration of 50% PV coverage besides lower yield by the high PV percentage coverage. Cho et al [147] detected lower weight and sugar content in grapes cultivated in Korea than those of the control group, delaying the harvest time about 10 days, and the sugar-content level present almost the same level as that of the control site. Conversely, some species including strawberry show good response in terms of quality (with higher chlorophyll content) and yield in comparison to unshaded treatment [55].…”
Section: Spatial Configuration Of Pv and Type Of Cropsmentioning
confidence: 94%
“…Bulgari et al [146] also found a lower content of quality parameters for tomatoes with a configuration of 50% PV coverage besides lower yield by the high PV percentage coverage. Cho et al [147] detected lower weight and sugar content in grapes cultivated in Korea than those of the control group, delaying the harvest time about 10 days, and the sugar-content level present almost the same level as that of the control site. Conversely, some species including strawberry show good response in terms of quality (with higher chlorophyll content) and yield in comparison to unshaded treatment [55].…”
Section: Spatial Configuration Of Pv and Type Of Cropsmentioning
confidence: 94%
“…Çalışmanın sonucunda panel verimliliklerinde ve ürünlerde dikkate değer bir farklılık gözlemlenmemiş, ancak test grupları altında yetişen üzümlerin gelişim süreçleri biraz uzamıştır. Üzümlerin içerdikleri şeker oranlarında da az miktarda değişim söz konusu olmuştur (Cho et al, 2020). Santra ve arkadaşları tarafından gerçekleştirilen bir başka çalışmada 0.5MW'lık elektrik üretim tesisinde, panellerin temizlenmesi için gerekli olan su miktarının 20.000 litre kadar olduğu bahsedilmiş ve panel altında yetiştirilmeye çalışılan tarım ürünlerinin bu temizlik amacı ile kullanılan sudan yararlanabileceği belirtilmiştir.…”
Section: Literatür çAlışmasıunclassified
“…Şekil 1. Agrivoltaic sistemin genel yapısı(Dos Santos, 2020) Agrivoltaic sistemlerde kullanılabilecek üç çeşit panel tipi vardır (Cho et al, 2020). Birincisi normal PV panelleri, Monokristal, Polikristal, İnce Film Güneş Panelleri, vb.…”
Section: Agrivoltaic Sistemlerin Türkiye'deki Potansiyeliunclassified
“…The electricity thus generated can be used to meet the farm needs and the surplus power can be sold. Crop cultivation and renewable energy production is possible and efficient wherein solar power can be generated in a crop production system like grapes [31].…”
Section: Solar Farmingmentioning
confidence: 99%